Properties of binder-bentonite-sand for construction of seepage cut-off walls - Widjaja, Melanie Chao Leng Yee (Nanyang Technological University, 2023)
Due to global warming, Singapore, a country surrounded by water bodies, becomes increasingly vulnerable to the negative consequences namely sea level rise. Most reclaimed land in Singapore is composed of sand material with high hydraulic conductivity. As such, there is a need to construct low-permeability seepage cut-off walls made of a mixture of in-situ sand, bentonite and binder to prevent seawater intrusion to be constructed in the sand layer. Conventional binders such as ordinary portland cement (OPC) have been incorporated previously and still widely in the construction of seepage cut-off walls. However, the usage of OPC has been deemed harmful towards the environment. In addition, workability and durability issues may arise when OPC is mixed with bentonites. Therefore, alternate binders such as ground granulated blastfurnace slag (GGBS) have been used and it has to be activated by magnesium oxide (MgO) and calcium oxide (CaO). When constructing seepage cut-off walls, the more important factors are strength and permeability. As such, this Final year project aims to evaluate the properties of sand-bentonite-binder mixtures. To evaluate these properties, seawater was added during sample preparation and these samples underwent tests such as unconfined compression tests, permeability tests and scanning electron microscope. Unconfined compression tests were conducted on Day 14, 28, 56 and 112, whereas permeability tests were carried out on Day 56. Through tests, it was determined that binder MgO:GGBS(1:9) in all bentonite types obtained the highest unconfined compression strength (UCS) and the permeability values have all passed the acceptable design limit. This suggests potential in using MgO:GGBS as a binder in sand-bentonite-binder mixtures in seepage cut-off walls in seawater environment.